1994
DOI: 10.1002/mc.2940090107
|View full text |Cite
|
Sign up to set email alerts
|

G→A mutations in p53 and Ha‐ras genes in esophageal papillomas induced by N‐nitrosomethylbenzylamine in two strains of rats

Abstract: In human esophageal cancers, no ras gene mutations but a relatively high prevalence of p53 gene mutations have been reported. We found a high prevalence of point mutations in Ha-ras and p53 genes in N-nitrosomethylbenzylamine (NMBA)-induced esophageal tumors in two strains of rats (BD VI and F344). Our analysis showed the point mutation GGA-->GAA (expected from the known mechanisms of action of NMBA) at Ha-ras codon 12 in 22 of 46 (48%) and 22 of 38 (58%) papillomas from BD VI and F344 rats, respectively. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 29 publications
3
29
0
Order By: Relevance
“…In contrast, the IARC mutation spectrum data on all gastric cancers document a higher frequency of 35.1% at CpG sites Vs 23.2% at nonCpG sites [IARC R12 release, 2007] [57]. Presence of alkyl nitrosamine in food stuffs, leading to O 6 -alkyl guanine adducts and base mispairing during replication, resulting in G>A (or C>T on the other strand of the DNA) transition [79] has been implicated in the etiopathogenesis of oesophageal and gastric carcinomas [80,81,82]. However, to establish a correlation between the enhanced tranvertions in our patients and the presence of carcinogens already reported or unreported to be present in the local food stuffs needs further investigations.…”
Section: Mutation Pattern Data (21) (%) Mutation Effect Data (21) (%)mentioning
confidence: 99%
“…In contrast, the IARC mutation spectrum data on all gastric cancers document a higher frequency of 35.1% at CpG sites Vs 23.2% at nonCpG sites [IARC R12 release, 2007] [57]. Presence of alkyl nitrosamine in food stuffs, leading to O 6 -alkyl guanine adducts and base mispairing during replication, resulting in G>A (or C>T on the other strand of the DNA) transition [79] has been implicated in the etiopathogenesis of oesophageal and gastric carcinomas [80,81,82]. However, to establish a correlation between the enhanced tranvertions in our patients and the presence of carcinogens already reported or unreported to be present in the local food stuffs needs further investigations.…”
Section: Mutation Pattern Data (21) (%) Mutation Effect Data (21) (%)mentioning
confidence: 99%
“…Additional evidence in support of this concept is the observation that transgenic rats carrying the human c-Ha-ras proto-oncogene are highly susceptible to the induction of esophageal tumors with NMBA (Asamoto et al, 2002). As has been found in human esophageal tumors, G:C→ A:T transition mutations have been observed in the p53 tumor suppressor gene in ∼30 % of rat esophageal papillomas (Lozano et al, 1994;. These mutations have been found to be evenly distributed across the gene; no "hot-spots" were found for these mutations in the gene.…”
Section: Rat Esophageal Tumor Modelmentioning
confidence: 74%
“…Mutations in oncogenes and tumor suppressor genes in rat esophageal tumors are most likely due to formation of methylated guanine adducts in esophageal DNA. In contrast to human esophageal tumors, a large majority, between 60 and 100%, of NMBA-induced rat esophageal papillomas have a G:C→ A:T transition mutation in codon 12 of the H-ras gene (Lozano et al, 1994;). One study indicated that G →A mutations in codon 12 of the gene occur at very low frequency in early premalignant lesions of the esophagus and increase proportionately in lesions that progress to papilloma (Liston et al, 2000).…”
Section: Rat Esophageal Tumor Modelmentioning
confidence: 99%
“…Rat mammary and esophageal tumors caused by MNU and NMBA, respectively, are known to have high incidences of c-Ha-ras gene codon 12 mutations (GGA to GAA). [26][27][28] In contrast, mutations in the c-Ha-ras gene are rare in bladder or liver tumors induced by carcinogens in rats. [34][35][36] We have found that our Hras128 strain is highly susceptible to MNU-induced mammary, 9) N-butyl-N-(4-hydroxybutyl)nitrosamine-induced urinary bladder 37) and, in the present work, NMBA-induced esophageal carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…23,24) In line with this hypothesis, G to A mutations in codon 12 of c-Ha-ras are frequent in tumors induced by NMBA in rats. [25][26][27][28] Mammary carcinomas induced by N-methyl-N-nitrosourea (MNU) in rats also often demonstrate c-Ha-ras mutations. 29) We have reported the Hras128 rats carrying the same human c-Ha-ras proto-oncogene to be highly susceptible to mammary carcinogenesis induced by MNU, and we showed that the induced carcinomas contain minor popula- 3 To whom requests for reprints should be addressed.…”
mentioning
confidence: 99%